What makes self-managing organizations novel? Comparing how Weberian bureaucracy, Mintzberg's adhocracy, and self-organizing solve six fundamental problems of organizing - Frank Martela (Journal of Organization Design, 2019)
The bureaucratic organizational structure has been recently challenged by a number of organizations that claim to offer employee emancipation and autonomy through self-management, self-organizing, or "holacracy." To facilitate theorizing about such organizational-level self-management, I examine it as an ideal type of organizational form, comparing it to two more established organizational forms, Weberian bureaucracy and Mintzberg's adhocracy. More particularly, building on the four universal problems every organization needs to solve-two of which I divide into two sub-problems-I utilize a framework of six fundamental problems of organizing-task division, task allocation, rewarding desired behavior, eliminating freeriding, providing direction, and ensuring coordination-to demonstrate how these three forms of organizing have found different solutions to them. The radically decentralized model of authority at the heart of self-managing organizations is shown to lead to solutions to these problems that are based on peer-based accountability and rewarding, transparency of key information, and bottom-up emergent processes where employees have the authority and responsibility to identify necessary tasks and ensure that they get done. It is concluded that the self-managing organization indeed is a novel form of organizing that can better explain certain real-life organizational outliers than the existing paradigms of organizing. It is argued to be especially viable in industries where interdependence between units is low, outputs are highly tailored, and employee expertise and motivation are high. Accordingly, research on such organizations can offer several new insights relevant to both the practice and theory of organization design.
Keywords: 650; Adhocracy; Bureaucracy; Emancipation; Hierarchy; Motivation; Organizational design; Organizational theory; Self-management; Self-organizing